Internalisasi Karakter Religius Pada Siswi di Madrasah Ibtidaiyah Bahrul Ulum Tambak Beras Jombang - Puspita Sari, Jihan Ayu; Alaul Huda, Saihul Atho (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2023)
Education is one of the factors that shape a person's religiosity. Education at school, especially religious education, has a very large role in shaping a person's religiosity. The religious experience one obtains (has had) at school has a significant impact on a person's religious practice in everyday life. The aim of this research is to determine the formation of religious character in Madrasah Ibtidaiyyah Bahrul Ulum Tambak Beras Jombang students. This research is qualitative research, with data sources from teachers and students from Madrasah Ibtidaiyyah Bahrul Ulum Tambak Beras Jombang. The methods used in collecting data were observation, interviews and documentation. Qualitative data analysis with stages: data collection, data condensation, data presentation and conclusion drawing. The research results showed that at Madrasah Ibtidaiyyah Bahrul Ulum Tambak Beras Jombang, students also received yellow book studies to provide insight and knowledge related to good personality and character. Madrasah Ibtidaiyyah Bahrul Ulum Tambak Beras Jombang always supports and facilitates its students to always excel in both academic and non-academic fields.